KEBUTUHAN YANG BERKEMBANG DAN KETERBATASAN SUMBERDAYA PADA PRODUK JASA PENDIDIKAN - mudzakir, mudzakir (potensio, 2013)
Human needs are always evolving with the development of the environment occurs. While having limited resources to meet and keep up with the kebutuhaan. Education as a service products face the same problem, namely the growing educational needs and limited educational resources. Therefore, education implemented by adhering to the principles of economics, namely: (1) maximizing results -oriented process and minimization of risk, (2) efficiency, and (3) using economic calculation. Economic Education educational disciplines apply economic principles to analyze educational activities. Limited resources and even a relative scarcity implies that every resource use requires a careful choice of a limited group of possible choices. There are two kinds of approaches in the efficiency level of education, namely: (1) management approach, and (2) the economic approach. One unit of education can achieve efficiency in its implementation (based on a manager's educational achievement) consisting of (1) cost effectiveness (cost-effectiveness), and (2) external efficiency (cost benefit or cost benefit).Â Keywords: Needs, Resources, Efficiency